2013
DOI: 10.1186/1471-2458-13-752
|View full text |Cite
|
Sign up to set email alerts
|

Influence of integrated services on postpartum family planning use: a cross-sectional survey from urban Senegal

Abstract: BackgroundAlthough the majority of postpartum women indicate a desire to delay a next birth, family planning (FP) methods are often not offered to, or taken up by, women in the first year postpartum. This study uses data from urban Senegal to examine exposure to FP information and services at the time of delivery and at child immunization appointments and to determine if these points of integration are associated with greater use of postpartum FP.MethodsA representative, household sample of women, ages 15–49, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 14 publications
3
30
0
2
Order By: Relevance
“…This is true even among self-reported LAM users: a recent analysis of DHS data showed that many did not adhere to all three criteria for LAM effectiveness at the time of the survey [29]. Nevertheless, when postpartum women are exposed to postpartum family planning messages during other visits to health facilities, such as during labor and delivery, they are more likely to adopt a modern method [30,31]. In addition, community-based programs can increase the use of effective contraceptive methods in the postpartum period [32].…”
Section: Discussionmentioning
confidence: 80%
“…This is true even among self-reported LAM users: a recent analysis of DHS data showed that many did not adhere to all three criteria for LAM effectiveness at the time of the survey [29]. Nevertheless, when postpartum women are exposed to postpartum family planning messages during other visits to health facilities, such as during labor and delivery, they are more likely to adopt a modern method [30,31]. In addition, community-based programs can increase the use of effective contraceptive methods in the postpartum period [32].…”
Section: Discussionmentioning
confidence: 80%
“…Prior use of contraception was associated with postpartum contraception utilization which suggests that if women are educated about family planning options prior to pregnancy, this may improve their utilization postpartum for birth spacing [5]. Future interventions should also incorporate husbands since talking to husbands about family planning postpartum was associated with greater contraceptive utilization.…”
Section: Discussionmentioning
confidence: 99%
“…Policy and programming recommendations that promote integrating family planning and child immunization services are often based on insubstantial or con icting evidence about its impact on health services delivery and patient outcomes (20)(21)(22)(23). Given the scarcity of evidence and the resource and planning implications of integration, it is critical to develop context speci c evidence that captures the nature, extent, and effects of integration in order to inform policy and program design (9).…”
Section: Evidence and Measurement Gapsmentioning
confidence: 99%
“…Additionally, we reviewed the integration literature to identify facility-level attributes that support service integration. Several critical attributes emerged, including a) facility norms that support concurrent service provision (e.g., operational management standards and procedures that support the availability of both child immunization and family planning services at the same consultation or on the same day), and b) provider capacity to offer multiple services (e.g., provider(s) has the skills and willingness to offer family planning information or services during a child immunization visit) (22,26,(33)(34)(35)(36).…”
Section: Constructing and Interpreting The Indexesmentioning
confidence: 99%